West Indian nationhood and Caribbean integration : a collection of papers - Demas, William G. (CCC Pub. House BridgetownBB, 1974)
Looks at development, identity and unity in the Caribbean. Focuses on West Indian nationhood and provides some thoughts on the Caribbean Community.